An Evaluation of the Challenges and Limitations in the Adoption of Technological Innovations at Nnamdi Azikiwe International Airport - Abimbola J. KOLAWOLE; AbdulKodri G. ABDULRAFIU (FUDMA Journal of Engineering and Technology, 2025)
Nnamdi Azikwe International Airport, Abuja, recently adopted advanced technological innovations, despite the recent adoption, operational inefficiencies and passenger dissatisfaction persist. This raises concern about the effectiveness of these innovations in improving operational efficiency and passenger satisfaction at this airport. This study examined the effects of technological innovation on airport operations and passengers experience at Nnamdi Azikwe International airport Abuja, Nigeria. Data were collected through stratified random sampling from 380 passengers, population size of 5,484,839 and 376 airport operational staff with population size of 2758, through a structured questionnaire. The collected data was analysed using the descriptive and inferential statistics. The Unified Theory of Acceptance and Use of Technology (UTAUT) model was employed. Results on passengers show that technological innovation had a weak correlation with passenger perception and satisfaction, this was based on the holistic evaluation of the airport at (r = .015, p = .776) and with security and safety (r = .002, p = .972) while result on operational staff with (r = .051, p = .322) indicates a weak and statistically insignificant negative relationship between technological innovation and airport operations at Nnamdi Azikiwe International Airport (NAIA) this suggests that there is no strong relationship between airport operations and passenger perception on the effect of technological innovation at the airport. The study concludes that implementation of technological innovation depends on inclusion on operational staff in the adoption of technological equipment at the airport, regular staff training and continuous stakeholder engagement to overcome adoption barriers. The study recommended that, frontline staff should be involve in the selection and implementation of new technologies to aid seamless operational efficiency and passengers’ satisfaction.
Keywords: Technology, innovation, airport, operations, challenges.